Spontaneous Enantiomeric Enrichment of Chiral 1- (1-Naphthyl) Ethylamine - Elazar, Meyer (Technium BioChemMed, 2023)
An aqueous solution of the reaction product R-(+)-1-(1-naphthyl)ethylamine hydrochloride, having high enantiomeric excess, was spontaneously resolved into the two enantiomers by simple crystallization to afford the product in nearly 100% ee.